PELAKSANAAN PROGRAM RASKIN (BERAS UNTUK RAKYAT MISKIN) DI KELURAHAN PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Hamda, Rafika; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In the village there Pudu Causeway various obstacles and problems in the implementation of Raskin. Bengkalis Government has made a policy that is intended to ease the burden of spending Target Households (RTS) and help people to get out of the situation of the poor, but in reality there are many people who abuse these policies by not distributing Raskin appropriately, so that the main objectives of the policy not performing well. This study aims to determine the mechanism of implementation of Raskin in Sub Causeway Pudu and the factors that hinder the implementation of Raskin.The theory used in this research is the theory of poverty, empowerment theory, systems theory, and the theory of social action. This study used quantitative research methods deskripitif. Data collection techniques in this study was a questionnaire and in-depth interviews with respondents and key people who understand the issues Raskin will then be deduced.The results of this study indicate that the implementation of the program in the Village Causeway Raskin Pudu Mandau sub Bengkalis run ineffective. The indicators are running ineffective, among others: the right target, the right quantity, right quality, timely and appropriately priced. It is caused by factors inhibiting the implementation of RTS Raskin is data that is not valid, control the quantity, quality, time and price of rice distribution was rather overlooked by those who make policy.Keywords: Implementation, Barriers, Rice For The Poor (Raskin)